Compliant control of electric power assisted steering systems - (:unkn) unknown (SAE International, 2005)
In this study, a compliant control strategy is developed, which makes the application of position based control strategies practicable for electric power assisted steering systems. In order to do this, an additional virtual degree of freedom is added to the system, which is stimulated by the torque exerted on the steering wheel by the driver and the pinion position. The electro-actuator modeled on the second pinion of the steering gear is then commanded to position the pinion to the virtual system position using a traditional position control strategy. Thus, a compliance behavior is established that can be varied depending on the vehicle states and environmental conditions to improve the vehicle dynamics and safety of the passenger.